Methane emission reduction through hydrogen blending in a large bore 2-stroke lean-burn natural gas compressor engine - Vieira, Greg; Lorenzen, Rachel; Patterson, Mark; Olsen, Daniel (Frontiers in Fuels, 2024)
The impending and ever stringent emission regulations regarding natural gas compressor engines drives the research behind blending hydrogen with natural gas in an attempt at making these internal combustion engines, and their combustion process, more efficient. This investigation set out to answer two fundamental questions: will blending hydrogen with natural gas reduce the overall engine fuel consumption, and can greenhouse gas emissions be reduced by blending hydrogen with natural gas? A 4-cylinder Cooper-Bessemer GMV engine, housed at Colorado State University's Powerhouse facility, underwent hydrogen-natural gas blending investigations using multiple engine configurations. The lean-burn engine uses an active pre-combustion chamber as its ignition source, along with electronically activated high pressure fuel injection in the main combustion chamber. One configuration tested was utilizing the high pressure fuel injection and blending in hydrogen, up to 40% by volume, in both the main chamber and precombustion chamber fuel supplies. A second configuration where the main combustion chamber fuel was left as solely natural gas and only the pre-combustion chamber received the hydrogen blended natural gas was tested. The final configuration tested used low pressure fuel injection with mechanically actuated valves in the main chamber with a traditional spark plug ignition source being used. All engine configurations saw reductions in methane out emissions, up to a 30% reduction, using blended natural gas and hydrogen. Carbon dioxide emissions were also shown to reduce for two configurations. A reduction in brake specific fuel consumption, up to 2%, was also seen for two configuration. These results support the hypothesis that blending hydrogen into natural gas can reduce engine total fuel consumption and reduce greenhouse gas emissions.